2019
DOI: 10.1093/jisesa/iez073
|View full text |Cite
|
Sign up to set email alerts
|

Life-History Parameters of Striacosta albicosta (Lepidoptera: Noctuidae) Under Laboratory Conditions

Abstract: Striacosta albicosta (Smith) is a key pest of maize and dry beans in North America. It has expanded its distribution from the western Great Plains of the United States to the Great Lakes region in the United States and Canada. There has been limited research on the baseline biological aspects of this insect under controlled conditions. The objective of this study was to detail the biological parameters of S. albicosta feeding on an artificial diet under laboratory conditions. Overall survival from neonate to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 32 publications
3
12
1
Order By: Relevance
“…While we are unable to provide a precise explanation for the two flight peaks observed, insect emergence and crop development may have been affected by abnormal temperatures and variable precipitation observed both years , Andresen 2018. Our results are consistent with laboratory studies, which showed decreased survival of bean feeding larvae before the pupal stage of development when compared to larvae fed on corn (Montezano et al 2019). Combined with data presented in this study, these results suggest that the environmental factors experienced by the recently established western bean cutworm in Michigan may result in them being unable to fully develop on dry beans, in which case, dry beans may be acting as a regional sink host for this pest.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While we are unable to provide a precise explanation for the two flight peaks observed, insect emergence and crop development may have been affected by abnormal temperatures and variable precipitation observed both years , Andresen 2018. Our results are consistent with laboratory studies, which showed decreased survival of bean feeding larvae before the pupal stage of development when compared to larvae fed on corn (Montezano et al 2019). Combined with data presented in this study, these results suggest that the environmental factors experienced by the recently established western bean cutworm in Michigan may result in them being unable to fully develop on dry beans, in which case, dry beans may be acting as a regional sink host for this pest.…”
Section: Discussionsupporting
confidence: 92%
“…Previously, extension biologists have observed a preference for corn over dry beans when the corn has yet to tassel at the start of moth flight A third explanation may be that larvae have a low success rate developing and overwintering under dry bean cultivation due to various unknown environmental factors. For example, soil type has been suggested to affect prepupae development and survivability in previous laboratory studies and foliar insecticides tend to be used more frequently in dry beans than in corn (Montezano et al 2019, Difonzo et al 2015). While we are unable to provide a precise reason for our observed results, they still suggest that corn fields act as an efficient supply of adult moths for the western bean cutworm, maintaining successful mating populations in the region and perpetuating the damage on dry beans the subsequent growing season.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to several laboratory and field studies that reported high mortality rates for immature stage S. albicosta [1,6,34,35,36], where highest mortality was observed primarily during the prepupal period. In this study, the prepupal period also had the lowest survival rate, similar to larvae fed artificial diet [29]. Low prepupal survival may be associated with important changes required for metamorphosis and it is possible that laboratory conditions did not meet these requirements.…”
Section: Discussionmentioning
confidence: 87%
“…Experiments were conducted under laboratory conditions at the Agroecosystems Entomology Laboratory located at the West Central Research & Extension Center in North Platte, NE, USA. Biology studies were conducted with neonate larvae from egg masses laid by field-collected moths, following methods by [29]. Collections were made in 2017 near Grand Island, Nebraska, USA (40° 54’ 43.10” N, 98° 16’ 33.60” W).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation